The Reflection of Government Policy on Kurdish Journalism in Iraq (1969-1979) - Arazu Yousf Hassan; Azad Ubed Salih (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study deals with the history of the Kurdish press in Iraq during the years 1968-1979. The main purpose of it is to present the information, numbers, opinions and comments published by the Kurdish press regarding the policies of Arabization, displacement, executions and genocide pursued by the Baath Party government in Iraq towards the Kurds. The study also deals with the Kurdish underground press as an important source for studying the history of the Kurdish liberation movement in general and the position of the Iraqi government towards it. As well as highlighting the follow-up of the Kurdish secret press to what was published in the foreign press, and the memorandum of the United Nations and the Human Rights Organization on the policy of the Iraqi government towards the Kurdish people, and these follow-ups were published in a special corner in the Kurdish secret newspapers